A concurrent and prospective examination of the incongruous positive relationship between alcohol use and physical activity - Harkabus, Lindsey C., author; Harman, Jennifer J., advisor; Aloise-Young, Patricia, committee member; Merolla, Andrew, committee member; Dik, Bryan, committee member (Colorado State University. Libraries, 2012)
Research has demonstrated an incongruous positive relationship between alcohol consumption and physical activity concurrently among college students (Lisha & Sussman, 2010; Musselman & Rutledge, 2010). A goal of this research was to determine whether this relationship between alcohol use and physical activity exists, and whether different forms of physical activity share this relationship. Another purpose of this dissertation was to examine the potential moderating effects of several individual difference variables. Results revealed a positive association between alcohol use and moderate physical activity, as well as with two other forms of physical activity (leisure and domestic). In the longitudinal analyses, several factors moderated the relationship between moderate physical activity and alcohol use, with the relationship being stronger for male participants and for individuals who possess high levels of social motives. Opposite of my original hypotheses, several forms of physical activity demonstrated significant negative effects on alcohol use, including overall physical activity, vigorous physical activity, sports, and exercise. Overall, the results suggest the relationship between physical activity and alcohol use in college students is dependent on the type of physical activity being studied (e.g., vigorous versus moderate, sport versus leisure). Age moderated the negative effects of vigorous physical activity on alcohol use, with the effects being stronger for individuals older than 19 years. Implications for the prevention of alcohol use and abuse, improvement of physical activity behaviors, and studies of college physical activity interventions and alcohol use are discussed.
Keywords: alcohol; physical activity